Periostin mediates collagen production, ECM remodeling and myofibroblast differentiation in breast prosthesis capsule formation - Yang, Ying; Li, Shumo; Bian, Li; Dai, Xiaoming; Hu, Jun; Ma, Yun; Wang, Zhiyuan (Scientific reports, 2025)
Capsular contraction is the most common complication after breast augmentation or reconstruction, and is the main reason underlying patient dissatisfaction and additional subsequent surgeries. Periostin is an extracellular matrix protein and a member of TGF-β superfamily. Studies have shown that periostin is closely related to fibrosis, collagen cross-linking and tissue remodeling. In this study, we observed the expression of periostin and other fibrosis-related proteins in the capsule of human breast silicon implant, assessing their relationship with the extent of capsule fibrosis. By using human breast derived fibroblasts with manipulated periostin expression level, we explored periostin’s impact on other fibrosis-related cytokines, fibroblast proliferation, differentiation, and collagen synthesis. Furthermore, we employed a murine model of prosthesis implantation to elucidate the roles of periostin and lysyl oxidase (LOX) in capsule formation. Immunohistochemical analysis of clinical capsular specimens revealed a significant correlation between periostin expression levels and the severity of capsular contracture. In vitro experiments using human breast-derived fibroblasts demonstrated that periostin promotes fibroblast proliferation and regulates the expression of key fibrosis-related proteins such as LOX, BMP-1, fibronectin, and tenascin-C at both protein and mRNA levels. Moreover, periostin was found to induce fibroblast differentiation into myofibroblasts and enhance collagen production. In the murine model of prosthesis implantation, periostin and LOX were observed to increase the thickness of the prosthesis capsule, whereas the administration of the LOX inhibitor β-aminopropionitrile (BAPN) significantly attenuated capsule formation. Our study underscores the significant role of periostin in the pathogenesis of breast prosthesis capsule formation and contracture. These findings provide novel insights into the mechanisms underlying capsular contracture and suggest periostin as a potential therapeutic target for mitigating this complication.